Italian contribution to University Autonomy in Kazakhstan: the Erasmus+ project “Transition to University Autonomy in Kazakhstan” (TRUNAK) - Elena Azzolini; Maria Luisa Ricciardi; Vladimir Vukovic; Walter Ricciardi; Stefania Boccia; Stefania Bruno (Epidemiology, Biostatistics and Public Health)
Key words: university autonomy, higher education, Kazakhstan, Italy, TRUNAK, Erasmus plus.